Resveratrol mediated cancer cell apoptosis, and modulation of multidrug resistance proteins and metabolic enzymes - Readi, Mahmoud Zaki el; Eid, Safaa Yehia; Abdelghany, Ahmed Ali; Al-Amoudi, Hiba Saeed; Efferth, Thomas; Wink, Michael (Phytomedicine, 2019)
Background - The degree of intracellular drug accumulation by specific membrane transporters, i.e., MDR1, BCRP, and MRP, and the degree of detoxification by intracellular metabolic enzymes, i.e., CYP3A4 and GST, provide control for cancer chemotherapy through diminishing the propensity of cancer cells to undergo apoptosis which in turn modulates the unresolved and complex phenomenon of multidrug resistance (MDR) for the cancer cells. - Hypothesis/Purpose - This study dwells into the interaction details involving ABC-transporters, CYP3A4, GST and cytotoxic effects of resveratrol on different cell lines. - Methods - Resveratrol was evaluated for its ability modulating the expression and efflux functions of P-gp /MDR1, MRP1, and BCRP in the multidrug-resistant human colon carcinoma cell line, Caco-2, and CEM/ADR5000 cells through flow cytometry and RTPCR technique. - Results - The resveratrol influenced P-gp and MRP1 efflux functions whereby it increased rhodamine 123 with calcein accumulation in concentration-dependent manner (1 - 500 µM) in the Caco-2 cell lines and inhibited the effluxes of both the substrates also as concentration-dependent phenomenon (10 - 100 µM) in the p-gp overexpressing CEM/ADR5000 cells through FACS (full form). The treatment of drug-resistant Caco-2, and CEM/ADR5000 cells with doxorubicin (DOX) along with 20 µM of resveratrol in the mixture. It increased the cell sensitivity DOX towards the DOX and enhanced the cytotoxicity. The resveratrol inhibited both CYP3A4 and GST enzymatic activity in a concentration-dependent way and induced apoptosis in the resistance cell lines because of increased levels of caspase-3, -8,-6/9 and incremental phosphatidyl serine (PS) exposure as detected by flow cytometry. The treatment of Caco-2 cells with resveratrol showed significantly lower p-gp, MRP1, BCRP, CYP3A4, GST, and hPXR mRNA levels in a 48 h observation. - Conclusion - The result confirmed resveratrol mediated inhibition of ABC-transporters’ overall efflux functions, and its expression, and apoptosis as well as metabolic enzymes GST and CYP3A4 activity.